The Development Model of Store Atmosphere in Culiinary Business to Increase the Purchasing interest of Society in the Sub-Disctric of Percut Sei Tuan - Nel Arianty, S.E., M.M (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
-